Exploring the role of shared value on brand identity system amongst entrepreneurs in South Africa - Ngcobo, Luyanda (The IIE, 2019)
The aim of this research consisted the exploration of shared value in terms of what role it plays in the development and function of the brand identity system in relation to the entrepreneurs within South Africa. Thereafter, the researcher identified findings and then grouped them into three major themes which were explained and interpreted in relation to the previous literature and the theory. Moreover, this section will discuss the implications of the findings and evaluate whether the research was successful or not lastly, ethical considerations and limitations are discussed. Finally, there were points on the heuristic value of the research.
Keywords: Brand; Brand identity; Brand shared value; Entrepreneur; Entrepreneurship